Embedding service learning in European higher education - Aramburuzabala Higuera, Pilar; McIlrath, Lorraine; Opazo, Héctor (Routledge, 2019)
"Developed from the successful EU Erasmus+ funded project 'Europe Engage' this book promotes service-learning as a pedagogical approach that develops civic engagement within higher education. By bringing together a range of universities from across Europe and exploring the idea of the civic university through service-learning, this text presents a contemporary view of service-learning and community engagement. It provides conceptual and practical tools for teaching, researching and practicing service-learning and exposes service-learning as a key approach in terms of embedding a culture of political and civic literacy within higher education"--Resumé vydavatel
Keywords: sociální služby -- Evropa; dobrovolnictví -- Evropa; vysoké školy -- Evropa; vysokoškolské studium -- Evropa; vysokoškolští studenti -- Evropa; social service -- Europe; voluntarism -- Europe; universities and colleges -- Europe; college study -- Europe; college students -- Europe; elektronické knihy; sborníky; electronic books; papers of several authors